Ovarian response of Suffolk ewes to estrous synchronization using short-term protocol - Takada, Luciana [UNESP]; Bicudo, Sony Dimas [UNESP]; Rodrigues, Carlos Frederico de Carvalho; Coelho, Lia de Alencar; Mendes, Luiz Claudio Nogueira [UNESP]; Perri, Sílvia Helena Venturoli [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The efficacy of estrus synchronization using short-term protocol was evaluated by ultrasound exams in Suffolk ewes during the pre-breeding season. The control Group (n = 12) was synchronized by treatment for 12 days with vaginal sponges impregnated with medroxyprogesterone acetate, and 400 IU eCG at sponge withdrawal. Experimental groups I, II and III kept the sponge in place for 4 days, and 100 µg of PGF2a was administered at sponge withdrawal. Additionally, Group I (n = 12) had 0.1 mg of estradiol benzoate (EB) administered during sponge placement and 50 µg of GnRH 48 hours after sponge removal. Group II (n = 6) had 35 mg of progesterone (P4) injected, and 0.1 mg of EB administered during sponge placement, 400 IU eCG at withdrawal and 48 hours after, 50 µg GnRH were administrated. Group III (n = 12) had 35 mg of P4 and 0.2 mg of EB administered at sponge placement, 400 IU eCG at withdrawal, and 50 µg of GnRH was administrated after 56 hours. Ovaries were monitored through ultrasound scanning. Concerning the first wave, no difference was detected between the control group and the experimental groups. However, the characteristics of ovulatory wave were significantly different between the groups. The duration of the follicular wave was shorter for Group III than for Group II. The follicle in Group I reached its maximum diameter before the Group II. The diameter of the follicle at the sponge withdrawal in the control group was larger than in Group I. After sponge withdrawal, the follicular growth rate was smaller in the control group than in Group III. The maximum diameter of the follicle in Group II was larger than in the other groups. The short-term protocol in which estrogen was used did not synchronize the emergence of the wave of follicular development.
Keywords: eCG; estradiol benzoate; follicular dynamics; progesterone